Analisis dan Perancangan Sistem Informasi Akademik (SIAK) di STIKes Persada Husada Indonesia Jakarta Timur Tahun 2014 - Diana Barsasella; Dadang Mulyana (STIKes Persada Husada Indonesia, 2014)
IT developments grows more rapidly, signed by the integration of IT in various aspects of our life, one of them is education. One of the application of IT and IS in education is Academic Information System (SIAK). SIAK is a system that manages all academic activities. SIAK in STIKes PHI is still manual and not integrated, so there are many problems to the academic process. In the registration process at STIKes PHI, students may choose courses according Semester Credit Units (SKS) taken in the beginning of semester, but often there are problems such as schedules clash, or taking credits more than the incompatible with the IPS without checked by Lecturer. There are many mistaken happened of student’s attendance printing by the Academic Unit, for example the student take the course but the name are not listed on the attendance list, and vice versa. Process of KHS and transcripts is fairly slow, even is still commonly error in inputting courses and grades. This study was performed using the system development methodology Rapid Application Development (RAD) System Prototyping is to develop and implement information systems. RAD is one of the methods of system development with the System Development Life Cycle (SDLC). There are four basic steps in developing of information system that are planning, analysis, design, and implementation. In doing analysis and design of application program systems, the author use the tool of Unified Modeling Language (UML). The presence of this SIAK application program speed up the process and minimize errors that occur in the system as well as data storage process becomes more effective and efficient in database form, so it is expected to increase the effectiveness and efficiency in the management of academic data.